PENGARUH REKRUTMEN DAN PELATIHAN TERHADAPKINERJA KARYAWAN DEPARTEMEN PACKING FINISH GOOD PADA PT CEMINDO GEMILANG LEBAK, BANTEN - Edy Muhamad Hidayat; Muhamad Guruh (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study is to determine the effect of recruitment and training on employee performance at PT Cemindo Gemilang Lebak, Banten. The research method used is quantitative. The sampling technique used saturated sampling and the sample obtained in this study amounted to 80 respondents.  Data analysis was conducted using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing. The results of this study indicate that recruitment has a significant effect on employee performance, with a t-value (5.444) greater than the t-table value (1.991). Training also has a significant effect on employee performance, with a t-value (10.855) greater than the t-table value (1.991). Simultaneously, recruitment and training have a significant effect on employee performance, with the regression equation Y = 23.256 – 0.138X₁ + 0.556X₂. The coefficient of determination is 61.4%, which means that recruitment and training contribute 61.4% to employee performance, while the remaining percentage is influenced by other factors. The F-test results show that the F-value (61.298) is greater than the F-table value (3.96).